Bioprocessing and Fermentation Technology for Biomass Conversion - Adeline A. J. Wall; Harifara Rabemanolontsoa; Joachim Venus (Applied Sciences, 2023)
In an era where concerns about climate change intersect with the global energy crisis, there is a growing emphasis on alternative resources [...]